ISOLASI β-AMIRIN DARI KULIT BATANG PULAI BASUNG (Alstonia spatulata Bl.) - haiyul jurnal manager (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2015)
Alstonia spatulata Bl is a traditionally important medicinal plant. Roots, stems, leaves, and fruits of this genus have been used in traditionalmedicine to treat malaria, diarrhea, fever, fatigue, liver disease, dysentery, and diabetes. The aim of this research was to isolation and characterizationthe secondary metabolites of stem bark of A. spatulata . The result of fitochemistry test for the stembark of A. spatulata showed that it containssecondary metabolite of terpenoid and alkaloid groups. The result of isolation process yielded a white crystal of ASSB-C with n-heksan solution. Ithas melting point 196-198 0C. The analysis of 1H-NMR, 13C-NMR, HSQC, HMBC, COSY, NOESY and FT-IR spectra for ASSB-C showed that it isincluded into triterpenoid group which is called β-Amirin